Contrastive Study of Relativization in English and Persian Translation in Light of Mismatches in Julian House’s Model: A Case Study of Lord of the Flies - Mahdiyeh Sadat Miri (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
Translation is an important part of people's life in order to have communication and conception of other people's cultures. This research aimed to find the similarities and differences between two Persian translation, and also to found what mismatches occur in the translation. This research includes the source text by a well-known book, Lord of the Flies, and two Persian translations by Susan Ardakani and Nahid Shahbazi Moghadam. This research aimed to compare these two translations, and found the similarities and differences between them. After the comparison is accomplished, the researcher attempted to draw another comparison between these two translations and the original text based on House’s model of TQA. The research tended to find the mismatches of relativization in these two translations. Relativization includes who, which, and where and they refer to people, things, and places respectively. Relative clauses are the same both in Persian and English translations as a result; there are many mismatches, which happen in these kinds of translations. Therefore, the major aim of this research is to find the mismatches in these two Persian translations to understand which one is better and conveys a better meaning, and is more understandable based on House’s model of TQA. The research tended to find the mismatches of relativization in these two translations. Relativization includes who, which, and where and they refer to people, things, and places respectively. Relative clauses are the same both in Persian and English translations as a result; there are many mismatches, which happen in these kinds of translations. Therefore, the major aim of this research is to find the mismatches in these two Persian translations to understand which one is better and conveys a better meaning, and is more understandable based on House’s model.